The TEA domain transcription factors TEAD1 and TEAD3 and WNT signaling determine HLA-G expression in human extravillous trophoblasts - Bowen Gu; Leonardo M. R. Ferreira; Sebastian Herrera; Lara Brown; Judy Lieberman; Richard I. Sherwood; Torsten B. Meissner; Jack L. Strominger (Proceedings of the National Academy of Sciences, 2025)
Maternal–fetal immune tolerance guarantees a successful pregnancy throughout gestation. HLA-G, a nonclassical human leukocyte antigen (HLA) molecule exclusively expressed in extravillous trophoblasts (EVT), is a crucial factor in establishing maternal–fetal immune tolerance by interacting with inhibitory receptors on various maternal immune cells residing in the uterus. While trophoblast-specific cis-regulatory elements impacting HLA-G transcription have been described, the identity of trans-acting factors controlling HLA-G expression in EVT remains poorly understood. Utilizing a genome-wide CRISPR-Cas9 knockout screen, we find that the WNT signaling pathway negatively regulates HLA-G expression in EVT. In addition, we identified two trophoblast-specific transcription factors, TEAD1 and TEAD3, required for HLA-G transcription in EVT in a Yes-associated protein-independent manner. Altogether, we systematically elucidated essential genes and pathways underlying HLA-G expression in EVT, shedding light on the mechanisms of maternal–fetal tolerance and potentially providing insights into controlling HLA-G expression beyond EVT to protect allogeneic cells from immune rejection.